The Influence of Workload and Organizational Culture on Employee Work Productivity at PT. Sinar Terang Madani, Makassar City - Wahyu, Trie Setria (Maroon Journal De Management, 2025)
The purpose of this study was to determine the effect of workload and organizational culture on employee work productivity at PT Sinar Terang Madani in Makassar City. The type of research used is quantitative with a descriptive approach. obtained through a questionnaire then processed quantitatively using a Likert scale, which was analyzed using multiple regression analysis tools to determine how the effect of workload and organizational culture on employee work productivity. determination coefficient analysis is used to determine how much proportion of the influence of workload and organizational culture on employee work productivity. The T test is used to answer the hypothesis. The results of this study indicate that the workload variable and the organizational culture variable (organizational family) have a positive and significant effect on employee work productivity and the large proportion of the influence of workload and organizational culture on employee work productivity with an R square value of 0.557 means the influence of the workload variable and organizational culture (organizational family) 55.7 percent. The relationship between workload and organizational culture (organizational family) is at a strong relationship level.